2013
DOI: 10.1038/nrmicro3161
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion, invasion and evasion: the many functions of the surface proteins of Staphylococcus aureus

Abstract: Staphylococcus aureus is an important opportunistic pathogen and persistently colonizes about 20% of the human population. Its surface is ‘decorated’ with proteins that are covalently anchored to the cell wall peptidoglycan. Structural and functional analysis has identified four distinct classes of surface proteins, of which microbial surface component recognizing adhesive matrix molecules (MSCRAMMs) are the largest class. These surface proteins have numerous functions, including adhesion to and invasion of ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
1,193
0
18

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 1,212 publications
(1,272 citation statements)
references
References 145 publications
7
1,193
0
18
Order By: Relevance
“…A variety of cell-surface components are involved in intercellular interactions (2,3). Although the polycationic polysaccharide intercellular adhesin has long been thought to be the main component promoting intercellular adhesion (4,5), there is now a compelling body of evidence that cell wall-anchored (CWA) proteins are also involved (2,3). Several recombinant CWA proteins have been shown to form dimers in solution (6)(7)(8)(9).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…A variety of cell-surface components are involved in intercellular interactions (2,3). Although the polycationic polysaccharide intercellular adhesin has long been thought to be the main component promoting intercellular adhesion (4,5), there is now a compelling body of evidence that cell wall-anchored (CWA) proteins are also involved (2,3). Several recombinant CWA proteins have been shown to form dimers in solution (6)(7)(8)(9).…”
mentioning
confidence: 99%
“…A remarkable trait of this bacterium is its ability to form biofilms on implanted devices, thereby triggering infections that are difficult to treat with antibiotics (1,2). Biofilm formation is initiated by attachment of the bacteria to abiotic surfaces, protein-coated materials, and host cells, and followed by cell-cell adhesion and multiplication leading to a mature biofilm (1,2). A variety of cell-surface components are involved in intercellular interactions (2,3).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that S. aureus can secrete a wide range of proteins, including adhesins (4), nucleases (5,6), complement control proteins (7)(8)(9), and multiple toxins, which interfere with host immune function. Toxins elicit cytotoxicity toward a variety of cells ranging from epithelial cells to leukocytes (1,4,10), and their secretion is associated with lethality in some disease models (11)(12)(13)(14).…”
mentioning
confidence: 99%
“…Staphylococcus aureus have many different virulence factors, including Cell Wall-Anchored (CWA) proteins that have a vital role in pathogenesis and survival of S. aureus in the environment. Some of the CWA proteins are MSCRAMMs, which have a crucial role in colonization and binding to host extracellular matrix (ECM) (2,3). Many previous studies have suggested that CWA proteins such as ClfB, FnBPs, SasC, protein A, and sasG participate in biofilm formation, which is one of the bacterial approaches for pathogenesis and resistance against antibiotics (4)(5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%